KONTRIBUSI KEPEMIMPINAN KEPALA SEKOLAH, IKLIM ORGANISASI DAN PENGALAMAN MENGAJAR TERHADAP KOMITMEN GURU SMP NEGERI SE KECAMATAN SENTOLO KABUPATEN KULON PROGO (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This research is meant to know (1) the contribution of school leadership, organizational climate and teaching experience together on the Government Junior High School teacher commitment Sentolo Subdistrict of Kulon Progo Regency, (2) the contribution of school leadership to teacher commitment as the Subdistrict Sentolo Junior High School of Kulon Progo Regency, (3) organizational climate contributes to the commitment of the Government Junior High School teacher Sentolo Subdistrict of Kulon Progo Regency, (4) contribute to the experience of teaching the Government Junior High School teacher commitment Sentolo Subdistrict of Kulon Progo Regency.The population of this research consist of 126 teachers of the Government Junior High School Subdistrict Sentolo of Kulon Progo Regency . This research includes the study population as all teachers , amounting to 126 as respondents . The data obtained were analyzed using multiple regression .The results of the research show that the principal leadership , organizational climate and teaching experience has a positive and significant contribution to the teachers' commitment on the Government Junior High School Subdistrict of Kulon Progo Regency . The contribution of school leadership, organizational climate and teaching experience together the commitment of teachers is 64% . While the partial contribution of school leadership to teacher commitment by 20.12% . Contribution of organizational climate on teacher commitment by 22.60 % , while the teaching experience of the teachers' commitment is 21.12% .